From Justice to Politics: The Constitutional Court’s Role in Structured and Systematic Election Violations - Rofi Wahanisa; R. Benny Riyanto; Syahwal; Eko Mukminto; Uche Nnawulezi (Lex Scientia Law Review, 2025)
This research analyzes the judicial implications of the Constitutional Court’s rulings on structured, systematic, and massive (TSM) violations in Indonesian elections, and their impact on democratic integrity. Using a socio-legal approach, it combines legal analysis with social science perspectives to examine how the Court interprets and applies TSM principles within a broader socio-political context. The study finds that while the Constitutional Court plays a pivotal role in upholding electoral integrity and safeguarding democratic values, significant challenges remain. Chief among these is the difficulty of proving TSM violations, which are often entangled with powerful political interests. These challenges can weaken public trust, hinder accountability, and contribute to a democratic deficit. The study concludes that more robust judicial mechanisms and clearer evidentiary standards are needed to ensure fair adjudication and strengthen Indonesia’s democratic institutions.